Vertebral Osteomyelitis and Associated Stigma of Potts Disease; A Challenge to Diagnosis and Management in Developing World - Athar, Muhammad Hammad; Farid, Ummarah Zafar; Shoaib, Muhammad Shahbaz; Baqir, Khwaja Muhammad; Shamim, Babar; Masood, Abdullah Bin (Pakistan Armed Forces Medical Journal, 2025)
Our case was a 68-year-old male, known as hypertensive and prediabetic, who presented to the clinic with a two-week history of backache. The general physical and systemic examination was unremarkable except for tenderness at the L2-L3 region of the lower back. Laboratory workup showed markedly increased inflammatory markers along with decreased hemoglobin levels. A contrast-enhanced Magnetic resonance imaging of the lumbosacral spine was suggestive of either metastatic or infective etiology involving L2-L3 vertebral bodies. The possibility of metastatic disease was ruled out, and a Percutaneous CT-guided aspiration biopsy was performed. The culture of the discharge revealed the growth of streptococcus. Conservative management was advised and patient was started on IV antibiotics. Soon after, the patient began manifesting signs of deterioration, and contrast-enhanced Magnetic resonance imaging was repeated, suggestive of disease progression. Laminectomy, spinal fixation, and decompression surgery were performed immediately, and the patient was shifted to oral antibiotics postoperatively. Physiotherapy was advised, and the patient recovered without any complications.